The integration of safety and health aspects in chemical product design framework - Ten, Joon Yoon (2018)
Computer aided molecular design (CAMD) is a powerful technique to design molecules or chemical mixtures that fulfil a set of desirable target properties as specified by users. Molecular physical and thermodynamic properties are selected as the target properties to ensure that the designed molecules can achieve the property functionalities. However, the aspects of safety and health are not strongly emphasised as design objectives in many CAMD problems. In order to ensure that the synthesised molecule does not cause much harm and health-related risks to the consumers, it is critical to integrate both safety and health aspects as design factors in the current CAMD approaches.